2008
DOI: 10.1071/mf07125
|View full text |Cite
|
Sign up to set email alerts
|

Food resource variability in an Australian dryland river: evidence from the diet of two generalist native fish species

Abstract: To examine how food resource availability links with natural variation in primary productivity in the Moonie River, south-west Queensland, the diets of two native Australian fish species (Nematalosa erebi and Macquaria ambigua) were examined from fifteen waterholes in February, May and September 2006. N. erebi diets reflected strong ‘boom and bust’ patterns of food consumption, with high concentrations of benthic (non-filamentous) algae during boom (flow) times, moving to higher concentrations of filamentous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…See methods regarding missing data. The regression line indicates significant relationship opportunistically on Macrobrachium and zooplankton in the Moonie River (Sternberg et al 2008) and elsewhere (Pusey et al 2004;Balcombe et al 2005) so it is interesting to note that high prey availability during the study period was not reflected in a corresponding marked increase in the proximate body condition or biomass of M. ambigua. The lack of strong relationships is unexpected and suggests that whole body lipid content may be a rather crude surrogate for the physiological response of this species to increased food availability.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…See methods regarding missing data. The regression line indicates significant relationship opportunistically on Macrobrachium and zooplankton in the Moonie River (Sternberg et al 2008) and elsewhere (Pusey et al 2004;Balcombe et al 2005) so it is interesting to note that high prey availability during the study period was not reflected in a corresponding marked increase in the proximate body condition or biomass of M. ambigua. The lack of strong relationships is unexpected and suggests that whole body lipid content may be a rather crude surrogate for the physiological response of this species to increased food availability.…”
Section: Discussionmentioning
confidence: 94%
“…Adding to this, Collins and Anderson (1995) concluded that M. ambigua was, in relative terms, a "non-fatty fish". These observed low lipid levels may have masked any increases in body condition during the 'boom' period and may be an evolved trait in this species given the variability of food resources typical in these dryland systems Sternberg et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dietary plasticity and behaviour of generalist carnivores to switch between abundant prey suggest these species may be able to survive periods of variable prey abundances (Sternberg et al 2008). In contrast, the specialised diet of R. diversidens potentially makes this species more susceptible to significant changes in prey availability.…”
Section: Teleosts Polychaetesmentioning
confidence: 99%